Chinese temporal relation resolution based on Chinese-English parallel corpus. (2017) - Li, Lubiao; Zhang, Junsheng; He, Yanqing; Wang, Huilin
This paper studies the annotation of temporal objects such as EVENT-type and TIMEX3-type elements in Chinese text based on Chinese-English bilingual parallel corpus. We propose and implement a temporal relation resolution (TRR) engine for Chinese text. We use temporal recognition and normalisation tools to annotate the English text, and then map the annotations of English text to the Chinese text by word alignment. The constructed Chinese TimeBank could be used for TRR research based on TimeML in Chinese text.